Association of tumor-infiltrating lymphocytes with distant disease-free survival in the ShortHER randomized adjuvant trial for patients with early HER2+ breast cancer. (17th January 2019) - Dieci, M V; Conte, P; Bisagni, G; Brandes, A A; Frassoldati, A; Cavanna, L; Musolino, A; Giotta, F; Rimanti, A; Garrone, O; Bertone, E; Cagossi, K; et al.
Abstract: Background: There is the need to identify new prognostic markers to refine risk stratification for HER2-positive early breast cancer patients. The aim of this study was to evaluate the association of tumor-infiltrating lymphocytes (TILs) with distant disease-free survival (DDFS) in patients with HER2-positive early breast cancer enrolled in the ShortHER adjuvant trial which compared 9 weeks versus 1-year trastuzumab in addition to chemotherapy, and to test the interaction between TILs and treatment arm. Patients and methods: Stromal TILs were assessed for 866 cases on centralized hematoxylin and eosin-stained tumor slides. The association of TILs as 10% increments with DDFS was assessed with Cox models. Kaplan–Meier curves were estimated for patients with TILs ≥20% and TILs <20%. Median follow-up was 6.1 years. Results: Median TILs was 5% (Q1–Q3 1%–15%). Increased TILs were independently associated with better DDFS in multivariable model [hazard ratio (HR) 0.73, 95% confidence interval (CI) 0.59–0.89, P  =   0.006, for each 10% TILs increment]. Five years DDFS rates were 91.1% for patients with TILs <20% and 95.7% for patients with TILs ≥20% ( P  =   0.025). The association between 10% TILs increments and DDFS was significant for patients randomized to 9 weeks of trastuzumab (HR 0.60, 95% CI 0.41–0.88) but not for patients treated with 1 year of trastuzumab (HR 0.89, 95% CI 0.71–1.12; test for interaction P  =   0.088). For patients with TILs <20%, the HR for the comparison between the short versus the long arm was 1.75 (95% CI 1.09–2.80, P =0.021); whereas, for patients with TILs ≥20% the HR for the comparison of short versus long arm was 0.23 (95% CI 0.05–1.09, P  =   0.064), resulting in a significant interaction ( P  =   0.015). Conclusions: TILs are an independent prognostic factor for HER2-positive early breast cancer patients treated with adjuvant chemotherapy and trastuzumab and may refine the ability to identify patients at low risk of relapse eligible for de-escalated adjuvant therapy.